Evaluation of Site effects in sedimentary basins - Morales, J.; Luzón, F.; Palencia, V. J.; Sánchez Sesma, F. J.; García, J. M. (Física de la Tierra, 2002)
Different techniques to evaluate seismic site effects in sedimentary basins are reviewed. Broadly speaking, the methods used to analyse the seismic response of a certain place can be classified as empirical, semi-empirical and numerical. Empirical techniques basically estimate site effects with the data recorded by seismic stations, whereas semi-empirical methods use small earthquake records as empirical Green’s functions to simulate strong motion accelerograms. Among the numerical techniques we have distinguished three main groups of methods: a) Domain methods, b) Ray theories and Gaussian beams expansions, and c) Boundary methods. A selection of some of the contributions using these methods, with a wide set of references, is also presented for the interested reader.